Gelingensbedingungen non-formalen Lernens an außerschulischen Lernorten – Eine qualitative Interviewstudie mit Workshop-Moderator*innen - Reckmann, Eileen; Temmen, Katrin

„Das ist genau das richtige Setting“ ‒ Zusammen lehren und lernen im MINT-Cluster MINT4.OWL - Reckmann, Eileen; Blomberg, Tobias; Temmen, Katrin

Erste Ergebnisse aus einer Interviewstudie mit Workshop-Moderierenden mobiler Schülerlaborangebote an außerschulischen Lernorten - Reckmann, Eileen; Temmen, Katrin

Study of Electrically Excited Photon-Photon Resonances in Self-Injection-Locked Coupled-Cavity VCSELs - Lindemann, Markus (ORCiD: 0000-0002-2660-3497); Gerhardt, Nils C. (ORCiD: 0009-0002-5538-231X); Hofmann, Martin R. (ORCiD: 0000-0003-1265-0003); Shchukin, V. A.; Ledentsov, N. N.; Makarov, O. Y.; Zerova, V.; D’Alessandro, M.; Tibaldi, A.; Turkiewicz, J. P.

Developing a numerical modelling strategy for metallic pin pressing processes in fibre reinforced thermoplastics to investigate fibre rearrangement mechanisms during joining - Gröger, B.; Gerritzen, Johannes; Hornig, A.; Gude, M. (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
A numerical modelling strategy for the direct pin pressing process of metallic pins into continuous fibre-reinforced thermoplastic organosheets is developed. The joining process is performed above the thermoplast’s melting temperature, altering the initial material structure of the composite by fibre rearrangement, which in turn influences the load-bearing capacity of the joint. Therefore, the modelling strategy aims at predicting the resultant material structure after pin pressing. The modelling approach considers both the textile architecture and the process parameters (temperature, tool velocity). A sub-meso modelling framework for the fibres based on a multi-filament approach is used. The interaction between fibres and the thermoplastic melt, as well as the matrix flow, is modelled using the Arbitrary Lagrangian Eulerian method. This allows for the prediction of matrix-rich zones and fibre rearrangement around the pin. The promising results show a good agreement of the resultant material structure in terms of compaction and fibre volume content around the pressed pin. Characteristic parameters show an underestimation of the laminate thickness below the pin. Moreover, an evaluation method for evaluating the orientation changes of the virtual multi-filaments is developed and presented to observe and assess fibre rearrangement and fibre volume content in detail during the numerical process simulation. It can be seen that only fibres around the pin are displaced and not in the whole molten area. Furthermore, it can be observed in detail that the initial position of the fibres in relation to the pin determines whether the fibres are displaced in the in-plane or out-of-plane direction.

Direct parameter identification for highly nonlinear strain rate dependent constitutive models using machine learning - Gerritzen, Johannes; Hornig, Andreas; Winkler, Peter; Gude, Maik (ECCM21 - Proceedings of the 21st European Conference on Composite Materials)
Fiber reinforced plastics (FRP) exhibit strongly non-linear deformation behavior. To capture this in simulations, intricate models with a variety of parameters are typically used. The identification of values for such parameters is highly challenging and requires in depth understanding of the model itself. Machine learning (ML) is a promising approach for alleviating this challenge by directly predicting parameters based on experimental results. So far, this works mostly for purely artificial data. In this work, two approaches to generalize to experimental data are investigated: a sequential approach, leveraging understanding of the constitutive model and a direct, purely data driven approach. This is exemplary carried out for a highly non-linear strain rate dependent constitutive model for the shear behavior of FRP.The sequential model is found to work better on both artificial and experimental data. It is capable of extracting well suited parameters from the artificial data under realistic conditions. For the experimental data, the model performance depends on the composition of the experimental curves, varying between excellently suiting and reasonable predictions. Taking the expert knowledge into account for ML-model training led to far better results than the purely data driven approach. Robustifying the model predictions on experimental data promises further improvement.
Keywords: Direct parameter identification; Machine learning; Convolutional neural networks; Strain rate dependency; Fiber reinforced plastics; woven composites; segmentation; synthetic training data; x-ray computed tomography

A methodology for direct parameter identification for experimental results using machine learning — Real world application to the highly non-linear deformation behavior of FRP - Gerritzen, Johannes; Hornig, Andreas; Winkler, Peter; Gude, Maik (Computational Materials Science)

Corrosion behaviour of self-piercing riveted joints with uncoated rivets in high nitrogen steel - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Production Engineering)
Self-piercing riveting is an established joining technique for lightweight materials. To increase the sustainability of the rivet manufacturing process, the authors of the present paper have developed an approach for shortening the process chain by omitting the heat treatment and rivet coating. To do this, use is made of high nitrogen steel as the rivet material. Successful joining with these rivets has already been proven, and it has also been shown that a competitive joint strength can be achieved with these rivets. Up until now, no studies have been conducted of the corrosion behaviour of uncoated rivets in high nitrogen steel compared to conventional rivets made of heat-treatable steel with a coating of Almac® or zinc-nickel with topcoat, and the corrosion behaviour of joints manufactured with these rivets has also not been investigated. Furthermore, the suitability of rivets in high nitrogen steel for structures undergoing cathodic dip painting has not been evaluated to date. These are therefore the aims of the research work presented in this paper. Corrosion behaviour is tested by exposing rivets and joints to a salt spray atmosphere. Cross-cut tests are conducted in order to classify the adhesion of cathodic dip paint to the different rivet surfaces and materials. The results of the experimental test show that the cathodic dip paint has sufficient adhesion to the uncoated rivets in high nitrogen steel and that these rivets can therefore be used in the manufacture of car bodies. Due to the stainless properties of the high nitrogen steel, better corrosion resistance is seen by comparison to the commonly used coatings of Almac® and zinc-nickel with topcoat. A study of the corrosion behaviour of the joints shows that the rivet head diameter and rivet head position, in particular, are decisive for preventing crevice corrosion under the rivet head and contact corrosion within the joint.

Non-rotationally symmetric joints – Mechanisms and load bearing capacity - Devulapally, Deekshith Reddy; Martin, Sven; Tröster, Thomas (Materials Research Proceedings)
Abstract. Traditionally, joints are cylindrical and rotationally symmetric. In the present study, non-rotationally symmetric joints are used for joining steel and Glass mat-reinforced thermoplastic sheets (GMT). In addition, the study also analyzes the impact of non-rotational symmetric joint rotation on the load-bearing capacity. Single lap joint specimens were fabricated using the In-Mold assembly technique for joining steel sheets with GMT. Tensile shear tests were performed on different orientations of the joint geometry, and it was observed that changing the joint orientation influences the load-bearing capacity. The joints are constitutively modeled using beam elements and the influence of joint rotation on load distribution is examined through a static simulation study.

Schülerlabor ohne Schüler*innen und Labor – geht das? Neue Wege für das Schülerlabor - Reckmann, Eileen; Blomberg, Tobias; Temmen, Katrin

Disciplinarity as a Challenge for Innovation: Experiences from a Teaching Innovation Project - Sloane, Hannah Sabrina; Jenert, Tobias

Toward an Android Static Analysis Approach for Data Protection - Khedkar, Mugdha; Bodden, Eric (Proceedings of the IEEE/ACM 11th International Conference on Mobile Software Engineering and Systems (MOBILESoft '24). Association for Computing Machinery, New York, NY, USA, 65–68.)
Android applications collecting data from users must protect it according to the current legal frameworks. Such data protection has become even more important since the European Union rolled out the General Data Protection Regulation (GDPR). Since app developers are not legal experts, they find it difficult to write privacy-aware source code. Moreover, they have limited tool support to reason about data protection throughout their app development process. This paper motivates the need for a static analysis approach to diagnose and explain data protection in Android apps. The analysis will recognize personal data sources in the source code, and aims to further examine the data flow originating from these sources. App developers can then address key questions about data manipulation, derived data, and the presence of technical measures. Despite challenges, we explore to what extent one can realize this analysis through static taint analysis, a common method for identifying security vulnerabilities. This is a first step towards designing a tool-based approach that aids app developers and assessors in ensuring data protection in Android apps, based on automated static program analysis.
Keywords: static program analysis; data protection and privacy; GDPR compliance

“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Bodo Mrozek (2019/2021/2023): Jugend Pop Kultur. Eine transnationale Geschichte. Suhrkamp; Simon Reynolds (2023): Futuromania. Elektronische Träume von der Zukunft. Ventil. - Jacke, Christoph (Medien & Zeit. Kommunikation in Vergangenheit und Gegenwart.)
Keywords: Retromania Futuromania Popmusik Erinnerung Geschichte Transnationalität Elektronische Musik

Feste feiern - aber nachhaltig! Transdisziplinäre Festival Studies in aktuellen kultur- und gesellschaftspolitischen Kontexten. - Flath, Beate; Jacke, Christoph (Kulturpolitische Mitteilungen)
Keywords: Festivals; Popmusik; Kultur; Forschung; Livemusik

Marina Forell (2023): Atemlos zum Erfolg. Gender, Frauenbild und Entwicklungstendenzen im deutschen Schlager. - Jacke, Christoph (Musiktheorie. Zeitschrift für Musikwissenschaft.)
Keywords: Popmusik; Gender; Schlager; Frauen; Image; Deutschland

"Heute Disco, morgen Umsturz, übermorgen Landpartie" - Kurze Anmerkungen zu Pop-Gipfeln. - Jacke, Christoph
Keywords: Popmusic; culture; politics; Förderung; Forschung

Anti-Künste, Künste und das ganze Dazwischen: Nick Cave als prominente Figur der Popmusikkulturen - Jacke, Christoph; Kirschlager, Nils (Literaturpop. Zur pop- und rockmusikalischen Rezeption literarischer Texte.)

Zukunftspop - Popzukunft. Kurze Anmerkungen zu Konstanten der Popmusikkulturen. - Jacke, Christoph (Hits & Storys. 20 Jahre rock'n'popmuseum.)
Keywords: Zukunft; Popmusik; Medien; Technik; Genre; Wandel; Kulturen; Museum; Geschichte; Popular Music Studies